Root-sourced signal and photosynthetic traits, dry matter accumulation and remobilization, and yield stability in winter wheat as affected by regulated deficit irrigation - Ma, Shou-Chen; Duan, Ai-Wang; Wang, Rui; Guan, Zhong-Mei; Yang, Shen-Jiao; Ma, Shou-Tian; Shao, Yun (Agricultural water management, 2015)
•Regulated deficit irrigation (RDI) is important water-saving technique based on plants’ adaptive and specific responses to drought.•Appropriate RDI significantly increased drought resistance ability of winter wheat through improving the nHRS sensitivity of plants during progressive soil drying.•Appropriate RDI increased grain yield through increasing both current photosynthesis and the remobilization of pre-anthesis carbon reserves.•Appropriate RDI also increased water use efficiency (WUE) and yield stability of winter wheat. Regulated deficit irrigation (RDI) is important water-saving technique. Although some positive effects of RDI have been confirmed in earlier results, more knowledge is still need on how RDI can affect grain growth and drought ability of crops. A micro-plot field experiment was conducted under a movable transparent rain-shelter from October 2011 to June 2012. Three RDI treatments designed to subject the plants to soil water deficit at different stages: tillering-the beginning of the spring-growth stage (RS1), the beginning of the spring-growth to the end of stem elongation stage (RS2), and booting-heading stage (RS3). The results showed that RDI treatments improved the non-hydraulic root-sourced signal (nHRS) sensitivity and photosynthetic capacity of winter wheat. The soil water content (SWC) of RS1, RS2 and RS3 treatments when the nHRS was triggered and net photosynthetic rate (PN) declined significantly was significantly lower than the control during progressive soil drying. After flowering stage, RS1 and RS2 treatments had significantly lower post-flowering accumulated dry matter (ADM), and but increased pre-flowering dry matter remobilization (DMR) in well-watered group, and both significantly increased DMR and ADM of wheat in dried group compared to the control. RS1 and RS2 had no significant effect on grain yield in well-watered group, but significantly increased grain yields in dried group. In addition, RS1 and RS2 also increased water use efficiency (WUE) and yield stability of winter wheat compared to the control. Above all, the results of this study showed that RS1 and RS2 treatments significantly increased drought resistance ability of winter wheat through improving the nHRS sensitivity of plants during progressive soil drying, and increased grain yield through increasing both current photosynthesis and the remobilization of pre-anthesis carbon reserves.